Kebijakan Penyetaraan Jabatan Fungsional di Lingkungan Kementerian Dalam Negeri: Efektivitas terhadap Kualitas Kinerja - Baharudin (Research and Development Agency Ministry of Home Affairs, 2023)
This study aims to explore the effectiveness and challenges of equalizing positions within the Ministry of Home Affairs (Kemendagri) from administrative positions to functional positions, which has caused a major transition in the field of government bureaucracy. This study answers three questions, namely, first, how is the policy implemented; second, what are the supporting and inhibiting factors; and third, how is work motivation due to equalization? This study used a qualitative method. Data was collected through interviews and secondary data. The research results showed that the policy of equalizing administrative positions into functional positions within the Ministry of Home Affairs in terms of implementing statutory regulations is smooth. However, problems arose when the policy was implemented. This problem can be seen in policy productivity, policy linearity, policy efficiency, and work motivation due to policy. This study suggests that the equalization of administrative positions into functional positions within the Ministry of Home Affairs should continue to be evaluated, and training related to the main duties and functions of each employee should continue to be improved.